The Body at the Service of Ideology: Physical and Sports Education in European Fascisms (Papeles, 2019)
This article aims to analyze how the fascist youth organizations used the youth body as a political symbol. Through the indoctrination of Hitler Jugend, the Opera Nazionale Balilla and Frente de Juventudes managed to get a social base of young people used as a symbol of loyalty to fascist political project. This text also aims to open new interpretive paths in the body’s themes - establishing it as a legitimate object of historical research.
Keywords: fascism; organizations; physical activity